EFL Majors’ Knowledge of Career Paths and the Job Market for English Graduates in Costa Rica - Loria Sanchez, Gloriana (2022)
The present study sought to ascertain the knowledge of English as a Foreign Language (EFL) majors of their career path possibilities and the job market for English graduates in Costa Rica. A total of 47 senior English students participated in this investigation. A questionnaire was administered to elicit the students’ knowledge of career paths and the job market for English graduates in Costa Rica and their familiarity with the orientation services provided by the University of Costa Rica. Main findings reveal inconsistencies in the knowledge of English majors of career paths and the job market in Costa Rica. Results also evince the undergraduates’ lack of familiarity with the services provided to help them improve their knowledge of those topics. Practical implications are discussed.